The Effect of Market Development on Sales Performance of Agro-Based Dealers in Nairobi City County, Kenya - Mukangai, Wycliffe Ingoi; Murigi, Elishiba Muthoni (Journal of Marketing and Communication, 2021)
Market development has been recognized as one of the strategies that improve sales performance of organizational products for decades. However, empirical research on the role of market development on improved sales performance of agricultural-based products is scanty. This study sought to investigate the relationship between market development and sales performance of agro-based dealers in Nairobi City County, Kenya. The study was anchored on the Ansoff matrix model and the push and pull theory. A descriptive research design was adopted and data was collected from 88 agro dealers in Nairobi City County using a closed-ended questionnaire. Both descriptive and inferential statistics were used to analyze the data. Reliability and validity were determined using Cronbach’s alpha value and expert opinion respectively. The results from multiple linear regression analysis revealed that marketing development (p=0.00; p<0.05) has a significant relationship with sales performance of the agro-dealers in Nairobi City County. Based on these findings, it was concluded that agro-based companies have the potential to enhance their performance in their markets through deliberate implementation of market development. This study recommends that agro-dealer firm managers should embrace market development as a strategy to increase their sales performance. Keywords: Market Development, Sales Performance, Agro-Based Dealers & Kenya.